Battery and method for manufacturing battery

By providing a resin coating and an intermediate layer in the negative electrode of the battery, or setting a concentration gradient layer, the problem of the negative electrode current collector reacting with Li ions is solved, and the energy density of the battery is improved and the service life is extended.

CN119905633APending Publication Date: 2025-04-29TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411458304.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-10-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

When using aluminum as the negative current collector in the existing batteries, the negative current collector reacts with Li ions before the negative active substance, resulting in a decrease in discharge characteristics.

Method used

By providing a resin coating and an intermediate layer in the negative electrode, or the negative electrode active material layer is a concentration gradient layer, a structure in which the electrolyte layer and the negative electrode current collector do not come into direct contact, blocking the movement path of Li ions and avoiding the reaction of the negative electrode current collector and Li ions.

Benefits of technology

It effectively suppresses the reduction of discharge characteristics caused by the negative electrode current collector, improves the heat release and energy density of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905633A_ABST
    Figure CN119905633A_ABST
Patent Text Reader

Abstract

The invention relates to a battery and a manufacturing method of the battery. The main purpose of the present disclosure is to provide a battery in which a decrease in discharge characteristics caused by a negative electrode collector (Al collector) is suppressed. The present disclosure solves the problem by providing a cell having a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, the negative electrode having a negative electrode current collector as an Al current collector, and a negative electrode active material layer containing a negative electrode active material having a lower reaction potential than Al, the negative electrode current collector is coated with a resin coating layer containing a resin and a conductive material, and an intermediate layer containing the resin and the negative electrode active material is disposed between the resin coating layer and the negative electrode active material layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The present disclosure relates to batteries and methods of making batteries. Background Art In recent years, with the rapid popularization of electronic devices such as personal computers and mobile phones, the development of batteries used as their power sources has been advancing. In addition, in the automotive industry, the development of batteries for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) or electric vehicles (BEV) is advancing. For example, Patent Document 1 discloses a negative electrode for an all-solid-state battery, which includes a negative electrode collector layer and a negative electrode active material layer, wherein the negative electrode collector layer is an aluminum foil or an aluminum alloy foil. Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2022-085523 Summary of the invention Problems to be solved by the invention From the perspective of making the battery lightweight to achieve an increase in energy density, and improving the heat release of the battery to achieve the suppression of battery degradation, it is envisaged to use Al (aluminum) as the material of the negative electrode collector. On the other hand, since the reaction potential of Al is relatively high, when a material with a lower reaction potential than Al is used as the negative electrode active material, the negative electrode collector (Al collector) reacts with Li ions before the negative electrode active material, and the discharge characteristics are easily reduced. The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide a battery in which a decrease in discharge characteristics caused by a negative electrode current collector (Al current collector) is suppressed. Means for solving problems

[0001] A battery is a battery having a positive electrode, a negative electrode, and an electrolyte layer arranged between the positive electrode and the negative electrode, wherein the negative electrode has: a negative electrode collector as an Al collector, and a negative electrode active material layer containing a negative electrode active material having a reaction potential lower than that of Al, the negative electrode collector is coated with a resin coating containing a resin and a conductive material, and further, an intermediate layer containing the resin and the negative electrode active material is arranged between the resin coating and the negative electrode active material layer.

[0002] A battery is a battery having a positive electrode, a negative electrode, and an electrolyte layer arranged between the positive electrode and the negative electrode, wherein the negative electrode has: a negative electrode collector as an Al collector, and a negative electrode active material layer containing a negative electrode active material with a reaction potential lower than that of Al, and the negative electrode active material layer is a layer containing a resin, and is a concentration gradient layer in which the concentration of the resin increases from the electrolyte layer to the negative electrode collector side.

[0003] The battery according to [1] or [2], wherein the resin is a thermoplastic resin.

[0004] The battery according to any one of [1] to [3], wherein the reaction potential of the negative electrode active material is 0.3 V (Li + / Li) or less.

[0005] The battery according to any one of [1] to [4], wherein the negative electrode active material contains a Si-based active material or a carbon-based active material.

[0006] The battery according to [5], wherein the negative electrode active material contains the Si-based active material.

[0007] The battery according to any one of [1] to [6], wherein the electrolyte layer is a solid electrolyte layer containing a solid electrolyte.

[0008] The battery according to [1], wherein the resin coating layer does not contain the negative electrode active material.

[0009] The battery according to [1], wherein a ratio of the thickness of the intermediate layer to the total thickness of the negative electrode active material layer, the intermediate layer, and the resin coating layer is 0.80% or more.

[0010] The battery according to [1] or [9], wherein a ratio of the thickness of the intermediate layer to the total thickness of the negative electrode active material layer, the intermediate layer, and the resin coating layer is 7.0% or less.

[0011] The battery according to [1], wherein the resin coating layer has a thickness of 10 μm or less.

[0012] A method for manufacturing a battery is a method for manufacturing a battery according to [1], comprising: a stacking body forming step of obtaining a stacking body having the Al collector, the resin coating and the negative electrode active material layer in sequence in the thickness direction; and a pressing step of applying pressing pressure to the stacking body in the thickness direction to form the intermediate layer.

[0013] A method for manufacturing a battery is a method for manufacturing the battery according to [2], comprising: a concentration gradient layer forming step of forming the concentration gradient layer on one surface of the Al current collector in a thickness direction. Effects of the Invention The present disclosure achieves the effect of being able to suppress the reduction in discharge characteristics caused by the negative electrode current collector (Al current collector). BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a schematic cross-sectional view illustrating a battery according to the present disclosure. Figure 2This is a schematic cross-sectional view illustrating a battery according to the present disclosure. Description of Reference Numerals 1…Positive electrode collector 2…Positive electrode active material layer 3…Negative electrode current collector (Al current collector) 4…Negative electrode active material layer 5…Resin coating 6…Middle Layer 7…Concentration gradient layer CA…positive electrode AN…Negative electrode EL…Electrolyte layer 10…Battery DETAILED DESCRIPTION The battery and the method for manufacturing the battery disclosed in the present invention are described in detail below. The figures shown below are schematically shown, and the size and shape of each part are exaggerated as appropriate for ease of understanding. In addition, in this specification, when indicating the way in which another component is configured for a certain component, when simply expressed as "upper" or "lower", unless otherwise specified, it includes both the situation in which another component is configured directly above or directly below a certain component in a manner connected to a certain component, and the situation in which another component is configured above or below a certain component via other components. A.Battery Figure 1 (a) is a schematic cross-sectional view illustrating a battery of the present disclosure. Figure 1 (b) Figure 1 (a) is a partially enlarged view. Figure 2 2 is a schematic cross-sectional view of a battery of the present disclosure. Figure 1 and Figure 2 As shown, the battery 10 of the present disclosure has a thickness direction D T The battery has a positive electrode CA, a negative electrode AN, and an electrolyte layer EL disposed between the positive electrode CA and the negative electrode AN. Figure 1 and Figure 2 As shown, the positive electrode CA generally includes a positive electrode current collector 1 and a positive electrode active material layer 2. The negative electrode AN includes a negative electrode current collector 3 which is an Al current collector and a negative electrode active material layer 4 containing a negative electrode active material having a lower reaction potential than Al. like Figure 1 As shown in (b), the negative electrode current collector 3 may be coated with a resin coating 5 containing a resin and a conductive material. Furthermore, in the negative electrode AN, an intermediate layer 6 containing the above resin and the above negative electrode active material may be arranged between the resin coating 5 and the negative electrode active material layer 4. Figure 2 As shown, the negative electrode active material layer 4 may be a layer containing a resin, and may be a concentration gradient layer 7 in which the concentration of the resin increases from the electrolyte layer EL toward the negative electrode current collector 3 side. According to the present disclosure, the negative electrode has a negative electrode active material layer, an intermediate layer and a resin coating, or the negative electrode active material layer in the negative electrode is a concentration gradient layer, so that the intermediate layer or the concentration gradient layer ensures the physical adhesion and conductivity of the interface of the negative electrode active material layer / resin coating, which helps to reduce the resistance at the interface, thereby becoming a battery that suppresses the reduction in discharge characteristics caused by the negative electrode collector (Al collector). As described above, from the perspective of making the battery lightweight to achieve an increase in energy density, and from the perspective of improving the heat release of the battery to achieve the suppression of battery degradation, it is envisaged to use Al (aluminum) as the material of the negative electrode collector. On the other hand, since the reaction potential of Al is relatively high, when a material with a lower reaction potential than Al is used as the negative electrode active material, the negative electrode collector (Al collector) reacts with Li ions and alloys before the negative electrode active material. Due to the damage of the collector accompanying the alloying, the discharge characteristics are easily reduced. In this regard, Figure 1 As shown, in the battery 10 in which the negative electrode AN has a negative electrode active material layer 4, an intermediate layer 6 and a resin coating 5, a structure is formed in which the electrolyte layer EL (the movement path of Li ions) is not in direct contact with the negative electrode collector 3 by using the resin contained in the intermediate layer 6 and the resin contained in the resin coating. The movement path of Li ions is blocked by the intermediate layer 6 and the resin coating 5, so that the movement of Li ions to the negative electrode collector 3 can be suppressed. Even in the potential range where Li ions react with the negative electrode collector 3 (Al collector) and alloy with lithium, since there are no Li ions near the surface of the negative electrode collector 3 (Al collector), the collector foil will not be damaged due to the alloying of the negative electrode collector 3 (Al collector). As a result, the reduction of the discharge characteristics caused by the negative electrode collector 3 (Al collector) can be suppressed. In addition, by providing the intermediate layer 6, the adhesion between the negative electrode active material layer 4 and the resin coating 5 becomes good by utilizing the anchor effect. As a result, the discharge characteristics are improved. On the other hand, Figure 2 As shown, in the battery 10 in which the negative electrode active material layer 4 is a concentration gradient layer 7, the proportion of the resin in the concentration gradient layer 7 increases as it approaches the negative electrode collector 3, so as to form a structure in which the electrolyte layer EL (the movement path of Li ions) is not in direct contact with the negative electrode collector 3, and the movement of Li ions to the negative electrode collector 3 can be suppressed. As a result, the reduction in discharge characteristics caused by the negative electrode collector 3 (Al collector) can be suppressed. In addition, when Li ions exist near the Al surface, the Al + ) alloying reaction with lithium occurs. +) is used as the negative electrode active material, due to the alloying reaction of Li and Al, Al is damaged, and the interface with the negative electrode active material layer 4 is peeled off and electrically insulated, and as a result, there is also a concern that the discharge characteristics will be reduced. In the present disclosure, the negative electrode has a negative electrode active material layer, an intermediate layer and a resin coating, or the negative electrode active material layer in the negative electrode is a concentration gradient layer, so that a structure is formed in which the electrolyte layer EL (the movement path of Li ions) is not in direct contact with the negative electrode collector 3, and Li ions no longer exist near the surface of the Al collector, which can suppress the alloying reaction of Al. 1. Negative electrode The negative electrode disclosed in the present invention includes a negative electrode current collector which is an Al current collector and a negative electrode active material layer containing a negative electrode active material having a reaction potential lower than that of Al. (1) Negative electrode collector The negative electrode current collector disclosed in the present invention is an Al current collector. The Al current collector is a current collector using aluminum (Al) as a material. The Al current collector preferably contains Al as a main material. The Al current collector may be Al alone or an Al alloy. In the Al alloy, the reaction potential of metal elements other than Al is preferably lower than that of Al. The ratio of the Al element to all metal elements is, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. On the other hand, in the Al alloy, the ratio of the Al element to all metal elements is, for example, 99 mol% or less. In addition, the shape of the Al current collector is, for example, foil and mesh. There is no particular limitation on the thickness of the Al current collector, for example, it is 1 μm or more and 50 μm or less. like Figure 1 As shown, the negative electrode current collector 3 which is an Al current collector may be covered with a resin coating 5 containing a resin and a conductive material. The resin coating contains resin. Examples of the above-mentioned resin include thermoplastic resins, thermosetting resins, and conductive polymers. Thermoplastic resins are resins that soften due to heat. The softening temperature of the thermoplastic resin is, for example, above 100°C and below 200°C, may be above 110°C and below 190°C, and may be above 130°C and below 180°C. Examples of thermoplastic resins include poly(meth)acrylic acid, polymethyl(meth)acrylate, polyethylene, polypropylene, polyethylene terephthalate, polyether nitrile, polyimide, polyamide, polytetrafluoroethylene, polyacrylonitrile, poly(meth)acrylate, and vinyl halide resin. It should be noted that "(meth)acrylic acid" is a concept that includes both acrylic acid and methacrylic acid, and "(meth)acrylate" is a concept that includes both acrylate and methacrylate. Examples of thermosetting resins include epoxy resins, vinyl ester resins, unsaturated polyester resins, phenolic resins, and melamine resins. The resin coating generally contains a cured product of the thermosetting resin. In addition, examples of conductive polymers include polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylene vinylene, polyacrylonitrile, and polyoxadiazole. In addition, the resin contained in the resin coating may be one kind or two or more kinds. The resin contained in the resin coating is preferably a thermoplastic resin. This is because the thermoplastic resin softens due to heat, so the intermediate layer can be easily formed by, for example, a pressing process described later. In particular, the resin coating preferably contains at least one of poly(methyl)acrylate, poly(meth)acrylic acid and polyacrylonitrile as the above-mentioned resin. The above-mentioned resin may be a crystalline resin, an amorphous resin, or a mixture of the two. From the viewpoint of adhesion, the above-mentioned resin is preferably an amorphous resin. Furthermore, the so-called "crystallinity" of a resin refers to an endothermic peak having a half-width of less than 10°C when measured at a heating rate of 10 (°C / min) in differential scanning calorimetry (DSC measurement). On the other hand, the so-called "amorphous" of a resin refers to a half-width of more than 10°C or no clear endothermic peak is confirmed. The resin contained in the resin coating layer may be the same resin as the binder contained in the negative electrode active material layer described later, or may be a different resin. In addition, the resin contained in the resin coating layer may not be a fluorine-containing resin such as PVdF. The resin coating contains a conductive material. Examples of the conductive material include carbon materials. Examples of the carbon material include acetylene black (AB) and Ketjen black (KB) and other particulate carbon materials; and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNTs) and carbon nanofibers (CNFs). The proportion of the conductive material in the resin coating is, for example, 1 part by weight or more and 50 parts by weight or less, 5 parts by weight or more and 40 parts by weight or less, or 10 parts by weight or more and 30 parts by weight or less, relative to 100 parts by weight of the resin. In addition, the resin coating preferably does not contain the negative electrode active material described later. Similarly, the resin coating preferably does not contain the electrolyte described later, especially the solid electrolyte. The resin coating usually covers at least the surface (first surface) on the electrolyte layer side of the Al current collector in the thickness direction. The resin coating may also cover the surface other than the first surface of the Al current collector. When viewed from the thickness direction, the proportion (coverage) of the portion covered by the resin coating in the first surface is, for example, 50% or more, 70% or more, or 90% or more. On the other hand, the coverage may be 100%, less than 100%, or less than 95%. The linear expansion coefficient of the resin coating is not particularly limited, and is, for example, 100×10 -6ppm / K or more and 500×10 - 6 ppm / K or less, can be 200×10 -6 ppm / K and above 430×10 -6 ppm / K or less, can be 230×10 -6 ppm / K or above and 350×10 -6 ppm / K or less. The value of the linear expansion coefficient is a value measured by a method in accordance with JIS H7404-1993. The thickness of the resin coating is not particularly limited, and may be, for example, 0.5 μm or more, 1.0 μm or more, 3 μm or more, or 4 μm or more. On the other hand, the thickness of the resin coating may be, for example, 10 μm or less, 8 μm or less, or 6 μm or less. (2) Negative electrode active material layer The negative electrode active material layer contains a negative electrode active material having a reaction potential lower than that of Al. The reaction potential of the negative electrode active material is not particularly limited as long as it is lower than the reaction potential of Al. For example, it is 0.3 V (Li + / Li) or less, can be 0.2V(Li + / Li) or less, can be 0.1V(Li + / Li) or less. On the other hand, the reaction potential of the negative electrode active material is, for example, -0.5 V (Li + The reaction potential of the negative electrode active material can be obtained by cyclic voltammetry (CV). As the negative electrode active material, for example, Si-based active materials, carbon-based active materials, and Li-based active materials can be listed. Si-based active materials are active materials containing Si elements. For example, Si-based active materials can be listed as Si single substance, Si alloy, and Si oxide. Si alloy preferably contains Si element as the main component. The proportion of Si element in Si alloy is, for example, 50 mol% or more, 70 mol% or more, and 90 mol% or more. On the other hand, the proportion of Si element in Si alloy is, for example, 99 mol% or less. As Si alloys, for example, Si-Al alloys, Si-Sn alloys, Si-In alloys, Si-Ag alloys, Si-Pb alloys, Si-Sb alloys, Si-Bi alloys, Si-Mg alloys, Si-Ca alloys, Si-Ge alloys, Si-Pb alloys, etc. can be listed. Si alloys can be two-component alloys or three-component or more alloys. As Si oxides, for example, SiO can be listed. The carbon-based active material is an inorganic active material containing the element C, and examples thereof include graphite, hard carbon, and soft carbon. In addition, the Li-based active material is an active material containing the element Li, and examples thereof include simple Li and Li alloys. The shape of the negative electrode active material may be, for example, a particle shape or a layer shape. The average particle size (D 50 ) is, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D 50 ) refers to the cumulative 50% particle size in a volume-based particle size distribution obtained using a laser diffraction particle size distribution measuring apparatus. The negative electrode active material layer may contain at least one of a conductive material, a binder and an electrolyte as required. As binders, for example, rubber-based binders such as butadiene rubber (BR), acrylic butadiene rubber (ABR) and styrene butadiene rubber (SBR); and fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). For the conductive material, it is the same as described in the above-mentioned "(1) Negative electrode collector". On the other hand, for the electrolyte, it is the same as described in the later-described "3. Electrolyte layer". like Figure 2 As shown, the negative electrode active material layer 4 is a layer containing a resin, and may be a concentration gradient layer 7 in which the concentration of the resin increases from the electrolyte layer EL toward the negative electrode current collector 3. The resin is the same as the above-mentioned resin. like Figure 2 As shown, in the negative electrode active material layer 4 (concentration gradient layer 7), the surface on the side opposite to the negative electrode collector 3 is the first surface S1, and the surface on the negative electrode collector 3 side is the second surface S2. In this case, the concentration C1 of the resin in the first surface S1 is smaller than the concentration C2 of the resin in the second surface S2. The ratio of C1 to C2 (C1 / C2) is, for example, greater than 0.1, may be greater than 0.3, or may be greater than 0.5. On the other hand, C1 / C2 is, for example, less than 0.9, or may be less than 0.7. The concentration of the resin in the concentration gradient layer may increase continuously from the first surface S1 to the second surface S2, or may increase in stages. In addition, the second surface may be in contact with the Al current collector, or may be in contact with the resin coating covering the Al current collector. In addition, when the second surface is observed from the thickness direction, the proportion of the resin in the concentration gradient layer may be, for example, 80% or more and 100% or less, or 90% or more and 99% or less. The thickness of the negative electrode active material layer is not particularly limited, and is, for example, 0.5 μm or more and 1000 μm or less. (3) Middle layer The negative electrode disclosed in the present invention may have an intermediate layer between the resin coating layer and the negative electrode active material layer. By providing the intermediate layer, the adhesion between the resin coating layer and the negative electrode active material layer is improved. The intermediate layer contains the negative electrode active material contained in the negative electrode active material layer and the resin contained in the resin coating layer. The intermediate layer is typically a layer in which a portion of the negative electrode active material (one particle) contained in the negative electrode active material layer penetrates into the resin coating layer, and a portion of the negative electrode active material (one particle) is mixed with the constituent components of the resin coating layer. Therefore, the intermediate layer may have a portion of the conductive material (one particle) contained in the resin coating layer. The negative electrode active material, the resin and the conductive material are as described in "(1) Negative electrode collector" and "(2) Negative electrode active material layer", respectively. In the cross section of the intermediate layer, the proportion of the resin is, for example, 10% or more and 90% or less relative to the total proportion of the negative electrode active material and the resin. In addition, in the intermediate layer, the above-mentioned proportion of the resin may be uniform in the thickness direction. On the other hand, the proportion of the resin may also change from the surface of the negative electrode active material layer side of the intermediate layer to the surface of the resin coating side. The proportion of the resin may be increased continuously or in stages, or may be decreased continuously or in stages, and the former is preferred. The ratio of the thickness of the intermediate layer to the total thickness of the negative electrode active material layer, the intermediate layer and the resin coating layer is, for example, 0.30% or more, 0.40% or more, 0.50% or more, 0.60% or more, 0.70% or more, 0.80% or more, 0.85% or more, 1.0% or more, or 1.5% or more. On the other hand, the above ratio is, for example, 7.0% or less, 6.6% or less, 6.0% or less, 5.0% or less, or 3.0% or less. The thickness of the intermediate layer is, for example, more than 10 nm, more than 30 nm, or more than 50 nm. On the other hand, the thickness of the intermediate layer is, for example, less than 1000 nm (1 μm), less than 800 nm, less than 600 nm, less than 400 nm, less than 300 nm, less than 200 nm, or less than 100 nm. The thickness of the intermediate layer is the average value of the thickness of any 10 points measured by observing the stacked cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) with an energy dispersive X-ray spectrometer (EDX). In addition, the components contained in the intermediate layer can be confirmed by using a scanning electron microscope (SEM) with an energy dispersive X-ray spectrometer (EDX) to perform EDX analysis on the chemical composition of the stacked cross section cut in the thickness direction of the above-mentioned intermediate layer. There is no particular limitation on the method for forming the intermediate layer. For example, when the resin in the resin coating is a thermoplastic resin, a method of heating the resin coating and the negative electrode active material layer to a softening temperature of the thermoplastic resin or higher and pressing them while the resin coating and the negative electrode active material layer are opposite to each other can be cited. On the other hand, when the resin in the resin coating is a thermosetting resin, a method of molding by filling a thermosetting resin and a negative electrode active material into a mold and heating them can be cited. 2. Positive electrode The positive electrode of the present disclosure generally includes a positive electrode active material layer and a positive electrode current collector from the electrolyte layer side. The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer may contain at least one of a conductive material, a binder, and an electrolyte as required. The conductive material, the binder, and the electrolyte are the same as those described in "1. Negative Electrode". Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and LiNi 0.8 Co 0.15 Al 0.05 O2 and other rock salt layered active materials, LiMn2O4 and other spinel active materials, LiFePO4 and other olivine active materials. In addition, sulfur (S) can be used as the positive electrode active material. The shape of the positive electrode active material is, for example, a particle shape. The thickness of the positive electrode active material layer is not particularly limited, and is, for example, 0.1 μm or more and 1000 μm or less. The positive electrode current collector is a member for collecting electrons from the positive electrode active material layer. The material of the positive electrode current collector is not particularly limited, and examples thereof include SUS, aluminum, nickel, iron, titanium, and carbon. Examples of the shape of the positive electrode current collector include foil and mesh. 3. Electrolyte layer The electrolyte layer is disposed between the positive electrode and the negative electrode, and more specifically, between the positive electrode active material layer and the negative electrode active material layer. The electrolyte layer contains at least an electrolyte. As an electrolyte, for example, a solid electrolyte can be cited. As a solid electrolyte, for example, inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes can be cited. The sulfide solid electrolyte preferably contains sulfur (S) as the main component of the anion element. The oxide solid electrolyte preferably contains oxygen (O) as the main component of the anion element. The halide solid electrolyte preferably contains a halogen (X) as the main component of the anion. Among these, a sulfide solid electrolyte is preferred. Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers. Z is any one of Ge, Zn, and Ga.) Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (Wherein, x and y are positive numbers. M is any one of P, Si, Ge, B, Al, Ga, and In.) As other examples of solid electrolytes, organic solid electrolytes such as polymer electrolytes and gel electrolytes can be cited. In addition, as the electrolyte, a liquid electrolyte (electrolyte) can also be used. In addition, the electrolyte layer of the present disclosure can be a layer in which the electrolyte is impregnated (impregnated) in the separator. The separator (separator) can be a conventionally known component. In the present disclosure, an electrolyte layer containing a solid electrolyte is sometimes referred to as a solid electrolyte layer, and a battery having a solid electrolyte layer is sometimes referred to as a full solid battery. In addition, the electrolyte layer may contain a binder as required. The binder is the same as described in "1. Negative electrode". The thickness of the electrolyte layer is, for example, 1 μm or more and 500 μm or less. 4. Battery The battery of the present disclosure may include an outer packaging body for accommodating the above-mentioned components. As the outer packaging body, for example, a laminated outer packaging body and a shell outer packaging body can be listed. In addition, the battery of the present disclosure may include a restraining fixture for imparting a restraining pressure in the thickness direction to the above-mentioned components. As the restraining fixture, a known fixture can be used. The restraining pressure is, for example, greater than 0.1 MPa and less than 50 MPa, and may be greater than 1 MPa and less than 20 MPa. There is no particular limitation on the type of battery disclosed in the present invention, and it is typically a lithium-ion secondary battery. In addition, the battery is preferably an all-solid-state battery. There is no particular limitation on the use of the battery, and for example, power sources for vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), electric vehicles (BEV), gasoline vehicles, and diesel vehicles can be cited. It is particularly preferred to be used as a driving power source for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), or electric vehicles (BEV). In addition, the battery disclosed in the present invention can be used as a power source for mobile bodies other than vehicles (such as railways, ships, and aircraft), and can also be used as a power source for electrical products such as information processing devices. B. Battery Manufacturing Method In addition, the present disclosure can provide a method for manufacturing the above-mentioned battery. Specifically, a method for manufacturing a battery having the above-mentioned negative electrode active material layer, an intermediate layer, and a negative electrode current collector (Al current collector) coated with a resin coating can be provided, the manufacturing method comprising: a stacking body forming step of obtaining a stacking body having the Al current collector, the resin coating, and the negative electrode active material layer in sequence in the thickness direction; and a pressing step of applying a pressing pressure to the stacking body in the thickness direction to form the intermediate layer. In the laminate forming step, the resin coating layer can be formed by applying a slurry containing a resin and a conductive material to an Al current collector and drying it. In addition, the negative electrode active material layer can be formed by applying a negative electrode slurry containing at least the above-mentioned negative electrode active material on the above-mentioned resin coating layer and drying it. In addition, the negative electrode active material layer can be formed by transferring on the resin coating layer using a transfer member having a negative electrode active material layer and a substrate. The laminate may include only the negative electrode active material layer, the resin coating layer and the Al current collector. Alternatively, the laminate may include an electrolyte layer on the side opposite to the negative electrode current collector, i.e., the Al current collector, or may include an electrolyte layer and a positive electrode. The pressing process is not particularly limited as long as the pressing pressure can be applied to the above-mentioned laminate to form the above-mentioned intermediate layer. The pressing conditions are, for example, the conditions described in the embodiments. The pressing pressure may be applied only once, or may be applied twice or more. As pressing methods, for example, roll pressing and cold isostatic pressing (CIP) may be cited. The pressing pressure is, for example, greater than 1 kN / cm and less than 100 kN / cm, and may be greater than 5 kN / cm and less than 80 kN / cm. In addition, in particular, when the resin is a thermoplastic resin, the above-mentioned pressing is preferably performed while heating the laminate. The heating temperature preferably takes into account the softening temperature of the thermoplastic resin, for example, greater than the softening temperature and less than the softening temperature + 100°C, and may be greater than the softening temperature and less than the softening temperature + 80°C. Furthermore, heating and pressing may be performed simultaneously or separately. In addition, the present disclosure can also provide a method for manufacturing a battery in which the negative electrode active material layer is a concentration gradient layer, the manufacturing method comprising: a concentration gradient layer forming step of forming the concentration gradient layer on one side of the Al current collector in the thickness direction. The concentration gradient layer forming step is not particularly limited as long as it can form the above-mentioned concentration gradient layer. The battery obtained by the above-mentioned steps is the same as described in "A. Battery". It should be noted that the present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and technical solutions having substantially the same configuration and achieving the same effects as the technical ideas described in the patent claims of the present disclosure are all included in the technical scope of the present disclosure. Example [Example 1] (Fabrication of positive electrode side laminate) A slurry containing a sulfide solid electrolyte (SE: Li2S-P2S5), a binder (acrylonitrile butadiene rubber (ABR) based binder) and a dispersion medium (heptane and butyl butyrate) was stirred using an ultrasonic disperser to obtain SE slurry. The weight ratio of SE and ABR based binder was adjusted to 99.4:0.6. The SE slurry was applied on a substrate (Al foil) using a doctor blade method and dried on a hot plate at 50°C for 1 minute. Then, it was further dried on a hot plate at 150°C for 30 minutes. Thus, a transfer component having a substrate (Al foil) and a solid electrolyte layer (SE layer) was obtained. Next, the positive electrode active material (NCA: LiNi 0.8 Co 0.15 Al 0.05 The slurry of NCA, SE, VGCF and PVdF binder was stirred by ultrasonic dispersion device to obtain positive electrode slurry. Among them, the weight ratio of NCA, SE, VGCF and PVdF binder was adjusted to 78.3:18.8:2.9:2.8. The positive electrode slurry was applied on the positive electrode collector (Al foil) by the doctor blade method and dried on a hot plate at 50°C for 20 minutes. Then, it was further dried on a hot plate at 150°C for 30 minutes. Thus, a positive electrode having a positive electrode collector and a positive electrode active material layer was obtained. The positive electrode and the transfer member were stacked so that the positive electrode active material layer and the solid electrolyte layer faced each other. They were pressed with a roller press at a pressure of 50 kN / cm and a temperature of 160°C. Then, the Al foil of the transfer member was peeled off and punched into 1 cm 2 Thus, a positive electrode side laminate having a positive electrode collector, a positive electrode active material layer and a solid electrolyte layer was obtained. (Fabrication of Negative Electrode Laminated Body) A slurry containing a sulfide solid electrolyte (SE: Li2S-P2S5), a binder (acrylonitrile butadiene rubber (ABR) based binder) and a dispersion medium (heptane and butyl butyrate) was stirred using an ultrasonic disperser to obtain SE slurry. The weight ratio of SE to ABR based binder was adjusted to 99.4:0.6. The SE slurry was applied on a substrate (Al foil) using a doctor blade method and dried on a hot plate at 50°C for 1 minute. Then, it was further dried on a hot plate at 150°C for 30 minutes. Thus, a transfer component having a substrate (Al foil) and a solid electrolyte layer (SE layer) was obtained. A resin slurry containing a vinyl resin (polymethyl methacrylate), a conductive material (carbon) and a dispersion medium was prepared. In the resin slurry, the ratio of the vinyl resin to carbon was 4:1 by weight. The resin slurry was applied on an Al foil using a doctor blade method and dried on a hot plate at 50°C for 20 minutes. Then, it was further dried on a hot plate at 150°C for 30 minutes. Thus, a negative electrode component having a negative electrode collector (Al foil) and a resin coating was obtained. In addition, the thickness of the negative electrode component was measured using a micrometer, and the thickness of the Al foil was subtracted from the thickness of the negative electrode component to calculate the thickness of the resin coating. The thickness of the resin coating is 2μm. Secondly, a slurry containing a negative electrode active material (silicon), a sulfide solid electrolyte (SE: Li2S-P2S5), a conductive material (vapor-grown carbon fiber: VGCF), a binder (PVdF-based binder) and a dispersion medium (butyl butyrate) was stirred using an ultrasonic dispersion device to obtain a negative electrode slurry. Among them, the weight ratio of silicon: SE: VGCF: PVdF-based binder was adjusted to 49:41.2:7.5:6.6. The negative electrode slurry was applied on the above-mentioned resin coating using a doctor blade method and dried on a hot plate at 50°C for 20 minutes. Then, it was further dried on a hot plate at 150°C for 30 minutes. Thus, a negative electrode having a negative electrode collector, a resin coating and a negative electrode active material layer was obtained. The negative electrode and the transfer member are stacked in such a way that the negative electrode active material layer and the solid electrolyte layer are opposite to each other. It is pressed with a roller press at a pressure of 50 kN / cm and a temperature of 160°C. Then, the Al foil of the transfer member is peeled off. Thus, a laminate having a negative electrode collector, a resin coating, a negative electrode active material layer, and a solid electrolyte layer is obtained. Next, the above-mentioned laminate and the transfer member are stacked in such a way that the solid electrolyte layers are opposite to each other. It is pre-pressed at 100 MPa and 25°C using a flat uniaxial press. Then, the Al foil of the transfer member is peeled off and punched into 1.08 cm 2 Thus, a negative electrode side laminate was obtained. (Fabrication of all-solid-state batteries) The positive electrode side laminate and the negative electrode side laminate were stacked so that the solid electrolyte layers faced each other and pressed using a flat uniaxial press at 200 MPa and 120° C. Thus, a battery (all-solid-state battery) was produced. [Example 2 and Example 3] A battery was produced in the same manner as in Example 1 except that the thickness of the resin coating layer in the negative electrode member was changed as shown in Table 1. The thickness of the resin coating layer was adjusted by changing the gap by the doctor blade method. [Example 4] First, a positive electrode was obtained in the same manner as in Example 1. The SE slurry prepared in Example 1 was applied twice by doctor blade method onto the positive electrode active material layer of the obtained positive electrode. Thus, a positive electrode side laminate having a positive electrode collector, a positive electrode active material layer, and a solid electrolyte layer was obtained. Next, a negative electrode slurry was obtained in the same manner as in Example 1. The obtained negative electrode slurry was applied on a substrate (SUS foil) and dried. Thus, a negative electrode transfer member having a SUS foil (substrate) and a negative electrode active material layer was obtained. The positive electrode side laminate was overlapped with the transfer member for the negative electrode so that the solid electrolyte layer and the negative electrode active material layer were opposite. This was pressed using a roller press at 50 kN / cm and 160°C. Then, the SUS foil was peeled off to obtain a laminate. This laminate was overlapped with the negative electrode member prepared in Example 2 so that the negative electrode active material layer and the resin coating were opposite, and pressed using a flat uniaxial press at 500 MPa and 160°C. Thus, a battery was prepared. [Comparative Example 1] A battery was produced in the same manner as in Example 1 except that the resin coating layer was not provided. [Evaluation 1] (Ratio of middle layer) Cross-sectional SEM images of the batteries produced in Examples 1 to 4 were obtained. By observing the SEM images, it was confirmed that an intermediate layer was formed in Examples 1 to 4. Furthermore, in the observed intermediate layer, the closer to the Al foil, the greater the proportion of the resin. In addition, based on the SEM images, the film thickness of the negative electrode active material layer, the film thickness of the intermediate layer, and the film thickness of the resin coating were measured, and the proportion (%) of the intermediate layer was calculated when the thickness from the negative electrode composite to the resin paste was set to 100. As a representative result, the proportion of the intermediate layer in Example 2 was 6.6%, and the proportion of the intermediate layer in Example 4 was 0.85%. (Cyclic test) The batteries produced in Examples 1 to 4 and Comparative Example 1 were subjected to a cycle test as described below, and the capacity retention rates were compared. First, the battery was clamped between two restraining plates, and the two restraining plates were fastened with fasteners. Thus, the distance between the two restraining plates was fixed. For the restrained battery, the initial charge and discharge were performed as follows. First, constant current charging was performed with 1 / 10C until 4.05V, then constant voltage charging was performed with 4.05V until the termination current was 1 / 100C, then constant current discharge was performed with 1 / 10C until 2.5V, and finally, constant voltage discharge was performed with 2.5V until the termination current was 1 / 100C. For the battery that was charged and discharged for the first time, a cycle test was carried out under the conditions of temperature 60°C, upper limit voltage 3.96V, lower limit voltage 2.89V, and 1 / 3C. The capacity of the 30th cycle was divided by the capacity of the 1st cycle, and the capacity retention rate (%) was calculated. The results of Comparative Example 1 were compared with relative values ​​set to 100. The results are shown in Table 1.

Table 1

Table 2

Claims

1. A battery comprising a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, The negative electrode comprises: a negative electrode current collector which is an Al current collector, and a negative electrode active material layer containing a negative electrode active material having a reaction potential lower than that of Al. The negative electrode current collector is coated with a resin coating layer containing a resin and a conductive material, and an intermediate layer containing the resin and the negative electrode active material is arranged between the resin coating layer and the negative electrode active material layer.

2. A battery comprising a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, The negative electrode comprises: a negative electrode current collector which is an Al current collector, and a negative electrode active material layer containing a negative electrode active material having a reaction potential lower than that of Al. The negative electrode active material layer is a layer containing a resin, and is a concentration gradient layer in which the concentration of the resin increases from the electrolyte layer toward the negative electrode current collector side.

3. The battery according to claim 1 or 2, wherein: The resin is a thermoplastic resin.

4. The battery according to claim 1 or 2, wherein The reaction potential of the negative electrode active material is 0.3V (Li + / Li) or less.

5. The battery according to claim 1 or 2, wherein The negative electrode active material contains a Si-based active material or a carbon-based active material.

6. The battery according to claim 5, wherein The negative electrode active material contains the Si-based active material.

7. The battery according to claim 1 or 2, wherein: The electrolyte layer is a solid electrolyte layer containing a solid electrolyte.

8. The battery according to claim 1, wherein The resin coating layer does not contain the negative electrode active material.

9. The battery according to claim 1, wherein The ratio of the thickness of the intermediate layer to the total thickness of the negative electrode active material layer, the intermediate layer, and the resin coating layer is 0.80% or more.

10. The battery according to claim 1, wherein The ratio of the thickness of the intermediate layer to the total thickness of the negative electrode active material layer, the intermediate layer, and the resin coating layer is 7.0% or less.

11. The battery according to claim 1, wherein The thickness of the resin coating layer is 10 μm or less.

12. A method for manufacturing a battery, which is a method for manufacturing the battery according to claim 1, comprising: A stacked body forming step of obtaining a stacked body having the Al current collector, the resin coating layer, and the negative electrode active material layer in this order in the thickness direction; and A pressing step of applying a pressing pressure to the laminate in the thickness direction to form the intermediate layer.

13. A method for manufacturing a battery, which is a method for manufacturing the battery according to claim 2, comprising: A concentration gradient layer forming step is to form the concentration gradient layer on one surface of the Al current collector in the thickness direction.

Citation Information

Patent Citations

  • All-solid battery negative electrode

    JP2022085523A